2020
DOI: 10.1038/s41598-020-59852-0
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensionality of Japanese kanji abilities

Abstract: the aim of this study was to identify the cognitive structures of kanji abilities in the Japanese general population and to examine age and cohort effects on them. From a large database of the most popular kanji exam in Japan, we analyzed high school graduation level data of 33,659 people in 2006 and 16,971 people in 2016. Confirmatory factor analyses validated the three-dimensional model of kanji abilities, including factors of reading, writing and semantic comprehension. Furthermore, the age effect on writin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…From the 12 levels of difficulty provided by Kanken, ranging from the easiest (Level 10) to the most difficult (Level 1, including Pre-2 and Pre-1), we employed the Level Pre-2 exam paper (mastery of 1951 daily-use kanji: high school level). Additionally, considering the possible ceiling effects in the Reading subtest 27 , we also conducted that subtest from the Level 2 exam paper (mastery of all 2136 daily-use kanji; high school graduation level). The results showed that only one participant achieved a perfect score on the Level 2 Reading subtest, whereas six participants did so on that of Level Pre-2.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 12 levels of difficulty provided by Kanken, ranging from the easiest (Level 10) to the most difficult (Level 1, including Pre-2 and Pre-1), we employed the Level Pre-2 exam paper (mastery of 1951 daily-use kanji: high school level). Additionally, considering the possible ceiling effects in the Reading subtest 27 , we also conducted that subtest from the Level 2 exam paper (mastery of all 2136 daily-use kanji; high school graduation level). The results showed that only one participant achieved a perfect score on the Level 2 Reading subtest, whereas six participants did so on that of Level Pre-2.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this conversion from kanji characters to kana letters is usually used in kanji education in Japan. Each correct item was given a score of 1, adding up to a maximum of 30 (0–30) 27 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations